Control Schemes in Queueing Networks - Brandwajn, A. (Management Science, 1976)
We consider open and closed queueing networks consisting of a set of controlled service centers. The controlled service center contains an exponential server, a queue of delayed customers and a control switch between them. The switch position is a function (control function) of the service center state which provides a means of controlling the service rate by admitting or not users into the server's queue. We give the stationary probability distribution for a broad class of control functions. An application of these results to the expected queue lengths and the expected waiting times in a two-server closed network is also considered.